2021
DOI: 10.1177/10732748211009252
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Cancer on Cancer Patients Treated at Hawassa University Comprehensive Specialized Hospital

Abstract: Cancer causes the highest economic loss of all of the leading 15 causes of death worldwide. The economic loss includes the loss of income and the expenses associated with health care costs. The Low awareness of the community toward cancer, the inadequacy of professionals and service providers, and the high budget consuming nature of the treatments are creating a great burden on the cancer patients. The objective of this study was to calculate patient side cancer treatment cost and to assess the contributing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…20,34 Similar studies conducted among another type of cancer patients showed that numerous patients are exposed to a high level of healthcare spending with considerable medical and transportation costs. 15,35,36 This might result because of limited physical access to cervical cancer treatment facilities and impaired productivity of patients as a result of their illness. This calls for expansion of service to regional towns, provision of support services such as transportation reimbursement, and health insurance scheme to the poorest patients may address the financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…20,34 Similar studies conducted among another type of cancer patients showed that numerous patients are exposed to a high level of healthcare spending with considerable medical and transportation costs. 15,35,36 This might result because of limited physical access to cervical cancer treatment facilities and impaired productivity of patients as a result of their illness. This calls for expansion of service to regional towns, provision of support services such as transportation reimbursement, and health insurance scheme to the poorest patients may address the financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a study conducted by Yen et al, (2015), in which supplements including fortified milk, multivitamins, etc contribute most (45%) to the direct non-medical cost. Besides supplemental food, transportation costs represent one of the main cost components in the non-medical cost category (Bona et al, 2021;Kong et al, 2020;Barwal et al, 2019;Zucca et al, 2011), which can be a barrier to accessing healthcare services. This is especially true for those in lower-income groups who live far away from the treatment sites.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cancer rehabilitation service costs in this hospital are covered by patients or their family members, similar to other health care services; however, cancer treatment is one of the services covered by health insurance. 26 , 28 …”
Section: Methodsmentioning
confidence: 99%